2011
DOI: 10.5812/iranjradiol.4494
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Clivus and Its Age-Related Changes in the Bone Marrow

Abstract: BackgroundThe clivus is a bone region between dorsum cella and foramen magnum. It can be evaluated very clearly in routine brain magnetic resonance imaging (MRI) dueto its central location.ObjectivesQuantitative and qualitative evaluation of the clivus and its changes according to age in a group of healthy people.Patients and MethodsThe transition of clival bone marrow to fatty marrow by the increasein age is examined by MRI in 105 men and 105 women who had no clival and bone marrow pathology on MRI. The clivu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…A uniformly high SI appeared in subjects after the age of 2 years and represented the majority at ages >15 years. Olcu et al [20] reported that the clivus/pons ratio on T1WI (CPR T1WI in our study) in normal children was about 1.0 (0.91-1.24) and increased with age. This finding is consistent with our results in normal subjects.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A uniformly high SI appeared in subjects after the age of 2 years and represented the majority at ages >15 years. Olcu et al [20] reported that the clivus/pons ratio on T1WI (CPR T1WI in our study) in normal children was about 1.0 (0.91-1.24) and increased with age. This finding is consistent with our results in normal subjects.…”
Section: Discussionmentioning
confidence: 61%
“…Age-related changes in SI on T1WI, which reflects the conversion from red to yellow marrow during growth, have been reported in clival bone marrow [10,[17][18][19][20]. The clivus showed a uniformly low SI in most infants under 1 year of age; the fractions of cases with a low SI decreased to 10 % in children aged 3-4 years and to 0 % in 6-year-olds [17].…”
Section: Discussionmentioning
confidence: 91%
“…This is referred to as "stage I" clivus bone marrow as opposed to stage II (intermediate stage with fatty infiltration of the marrow and the clivus has a heterogeneous appearance) or stage III (hypoactive marrow with a homogeneous hypoactive clivus). Olcu et al 10 found in their study that the stage III features were not noted in the age group of 0-9 years. In cases in which unexpected MRI clival changes are noted, as was the case with our patient, there is most likely an underlying pathology.…”
Section: Clinical Importance Diagnosis and Treatmentmentioning
confidence: 80%
“…The MRI features of bone marrow in the clivus have been seen to vary with age. 7,10,11 In childhood, the bone marrow is rich in hematopoietic tissue and the clivus is homogeneously hypointense. This is referred to as "stage I" clivus bone marrow as opposed to stage II (intermediate stage with fatty infiltration of the marrow and the clivus has a heterogeneous appearance) or stage III (hypoactive marrow with a homogeneous hypoactive clivus).…”
Section: Clinical Importance Diagnosis and Treatmentmentioning
confidence: 99%
“…Существует множество различных критериев установления возраста, но ни один из них вне связи с другими не может быть достаточно надежным при установлении возраста взрослых людей, так как они зави-сят от многих факторов, определяющих их высокую изменчивость [1,2]. Вопросы возрастной изменчивости турецкого седла [3,4] ската черепа (Блюменбахов скат) [5][6][7][8], размеров и взаиморасположение лобных [9,10] и клиновидной пазух, а также качественной оценки срединного атлантоосевого сустава (сустав Крювелье) остаются открытыми. В источниках литературы даны сведения об исследовании отдельных признаков, которые сгруппированы в самые различные возрастные группы, как правило, до 40-50 лет.…”
unclassified